Sliding vector fields via slow-fast systems - Llibre, Jaume (2008)
This paper concerns differential equation systems on ℝn with discontinuous right-hand sides. We deal with non-smooth vector fields in ℝ having a codimension-one submanifold M as its discontinuity set. After a regularization of a such system and a global blow-up we are able to bring out some results that bridge the space between discontinuous systems and singularly perturbed smooth systems.